Control of Pestivirus Infections in the Management of Wildlife Populations - Thomas Passler (Frontiers Research Topics, 2016)
Infections with recognized and putative species of the genus pestivirus are not host-specific and are documented in many wildlife species. The study of pestivirus infections in wildlife species is important both to eradication programs and programs for maintaining the health and well-being of wildlife populations. Free-ranging wildlife species may act as reservoirs for pestiviruses that infect domestic species. For this reason, eradication efforts for classical swine fever virus include control of the virus in wild boar populations. The contribution of free-ranging species to the circulation of BVDV1, BVDV2, and BDV is less well understood. While substantial damage due to pestivirus infections has been demonstrated in a few specific wildlife populations, the impact of pestiviral infections on the well-being of most captive and free-ranging wildlife populations is largely unknown. The research topics summarizes our current understanding of pestiviral infections in wildlife and discusses the challenges in understanding and mediating their impact on captive and free ranging wildlife species.